Fatigue Behavior of Reinforced Concrete Beams Strengthened With GFRP Sheets - K. A. Al-Saraj, Wissam (Journal of Engineering and Sustainable Development, 2007)
The objective of the presented study is to examine the effects of glass fiber reinforced polymer (GFRP) composite as rehabilitation systems on the fatigue performance of reinforced concrete beams. Experiments were conducted on beams with and without GFRP composite sheets on their tensile surfaces. The specimens were 152 X 152 X 1,321 mm reinforced concrete beams with enough transverse reinforcement to avoid shear failure. The results of this study indicate that the fatigue life of reinforced concrete beams with the given geometry, subjected to the same cycling load, can be significantly extended through the use of externally bonded GFRP composite sheets. An interesting finding is that, although the fiber strengthening system increases the fatigue life of the beams, the failure mechanism, and fatigue of the steel reinforcement, remains the same in both strengthened and non strengthened beams. Thus, it is possible to predict the fatigue life of a cyclically loaded beam using existing fatigue models.